Lebanon : 2009 Article IV Consultation and Assessment of Performance Under the Program Supported by Emergency Post-Conflict Assistance; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Lebanon. (IMF Staff Country Reports; Country Report, 2009)
The Lebanese financial system has so far weathered the global financial crisis. The 2009 Article IV Consultation highlights that deposit inflows decelerated briefly in the aftermath of the Lehman Brothers bankruptcy, but have resumed at a rapid pace since then. Executive Directors have welcomed the remarkable resilience of the Lebanese economy in the face of the global financial crisis. Directors have also supported the authorities' monetary policy aimed at safeguarding the exchange rate peg and facilitating a further buildup of international reserves.